2008
DOI: 10.1139/b07-138
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between mitochondrial electron transport, reactive oxygen species, and the susceptibility of Nicotiana tabacum cells to programmed cell death

Abstract: We investigated the impact of steady-state cellular reactive oxygen species (ROS) level on subsequent susceptibility to cell death induction by signaling molecules or respiratory inhibitors. We utilized Nicotiana tabacum L. ('Petit Havana SR1') suspension cell lines differing in steady-state ROS level owing to either genetic manipulation of the mitochondrial electron transport chain or manipulation of growth conditions. In either case, higher steady-state ROS level increased susceptibility to the signaling mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…2011). It has also been reported that complex III inhibitors with different sites of action display a differential ability to elicit cell death in tobacco cells (Robson, Zhao & Vanlerberghe 2008). More broadly, it is recognized that plant mitochondria are a target of P. syringae effector proteins (Greenberg & Vinatzer 2003; Block et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011). It has also been reported that complex III inhibitors with different sites of action display a differential ability to elicit cell death in tobacco cells (Robson, Zhao & Vanlerberghe 2008). More broadly, it is recognized that plant mitochondria are a target of P. syringae effector proteins (Greenberg & Vinatzer 2003; Block et al .…”
Section: Discussionmentioning
confidence: 99%
“…One such study, performed using isolated mitochondria from plant suspension cells, has suggested an impact of SA on the Q-cycle of complex III (de Souza et al 2011). It has also been reported that complex III inhibitors with different sites of action display a differential ability to elicit cell death in tobacco cells (Robson, Zhao & Vanlerberghe 2008). More broadly, it is recognized that plant mitochondria are a target of P. syringae effector proteins (Greenberg & Vinatzer 2003;Block et al 2010).…”
Section: Evidence That the Mitochondrion Is A Target Of Biotic Stressmentioning
confidence: 99%
“…Similarly, some of the pro‐survival functions described for H 2 O 2 (Torres, Jones & Dangl 2006) might be attenuated in the absence of conversion of mitochondrial O 2 ‐ to H 2 O 2 . We previously suggested that complex III‐derived O 2 ‐ could induce PCD in tobacco suspension cells, based on the disparate susceptibility of cells to two complex III inhibitors with differential capacities to generate O 2 ‐ (Robson, Zhao & Vanlerberghe 2008). Elucidating the functional importance of the mitochondrial O 2 ‐ burst clearly represents a rich area for further study.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, while ROS levels increased only transiently after ozone exposure in the WT plants, ROS levels increased and persisted in the AOX over-expressing plants. Amirsadeghi et al (2006) and Robson et al (2008) studied the response of N. tabacum plants and suspension cells to SA and nitric oxide, signaling molecules that are often implicated in biotic stress responses such as the hypersensitive response (a form of programmed cell death [PCD]). It was found that susceptibility to cell death by these signal molecules was dependent upon the steady-state cellular level of ROS and that AOX level was important toward establishing this steady-state level, likely due to its ability to influence the rates of ROS generation and/or scavenging.…”
Section: Impacts On Stress Tolerance and Cell Survivalmentioning
confidence: 99%
“…Amirsadeghi et al (2006) andRobson et al (2008) Low temperature stress (A. thaliana/leaves) Knockdown and over-expression of AOX1aAt low temperature (12 • C), knockdown of AOX1a reduced early shoot growth, whereas over-expression of AOX1a enhanced early shoot growthFiorani et al (2005) (A. thaliana/leaves) Over-expression of wheat AOX1a Over-expression of wheat AOX1a in A. thaliana delayed expression of the endogenous A. thaliana AOX1a gene following shift to low temperature (4 • C) Sugie et al (2006) (A. thaliana/leaves) T-DNA knockout of AOX1aAt low temperature (4-10 • C), knockout of AOX1a enhanced expression of ROS scavengers, increased C:N ratios and lowered lipid peroxidation levelsWatanabe et al (2008) …”
mentioning
confidence: 99%